Síntese de um novo agente de cura para resinas epóxi a partir da vanilina - Silva, Diego Leorne (2019)
Epoxy resins belong to the world9s second most used thermosetting class, falling behind to polyesters only. The epoxy polymers are used in aerospace and automobile industries. It is also employed in electronic components, adhesives, coatings, electronic laminates, and electronic devices. Although, in order to make use of these resins in all those industries they need to be polymerized. The polymerization process can be achieved with hardeners or, also called, curing agent. Hardeners possess electrophilic or nucleophilic character, and react with the epoxy rings by ring-opening reactions, which are highly reactive. Many chemical species may react with hardeners, such as amines, amides, hydroxyls, carboxylic acids, anhydrides acids, phenols, and Lewis acids. Among them, amines are the most exploited and the scarcest when it comes to renewable feedstock. In this state of affairs, the objective of this work is to develop a diamine derived from vanillin, an aromatic phenolic compound that can be obtained from lignin, the second most abundant biopolymer on the planet. To that, the vanillin was nitrated with calcium nitrate and glacial acetic acid to obtain the nitro-vanillin with 51% of yield. Secondly, nitrovanillin was reacted with hydroxylamine in acid medium to obtain nitro-oxime-vanillin with 53.3% yield. Finally, the nitro and oxime groups were reduced with by catalytic hydrogenation with Pd/C in acid medium, followed by basification to obtain vanillin-diamine with 65% yield. The synthetized molecules were characterized by 1H NMR, 13C NMR, FT-IR, and GC/MS. Vanillin-diamine was polymerized with the epoxy resin DGEBA and thermally analyzed by DSC and TGA, and compared with polymers o DGEBA and aliphatic and aromatic amines IPDA and PPD. The synthetized diamine showed higher thermal stability than the aliphatic diamine IPDA polymer and comparable with the aromatic diamine PPD polymer. The development of vanillin-diamine exhibits relevant importance in the environmental concerning theater that our society finds itself, hence it is biomass derived, and to the best of our knowledge, is the first diamine obtained from vanillin.